Chlorophyll - Jacob-Lopes, Eduardo; Queiroz Zepka, Leila; Isabel Queiroz, Maria (IntechOpen, 2017)
Chlorophyll presents an authoritative and comprehensive overview of the biology, biochemistry and chemistry of chlorophylls in photosynthetic organisms. Divided into seven discreet parts, the book covers topics on basic science and applied technology of chlorophyll molecules. Chlorophyll provides an insight into future developments in each field and extensive bibliography. It will be an essential resource for researchers and academic and industry professionals in the natural pigment field.